Low Crude Protein Diet Affects the Intestinal Microbiome and Metabolome Differently in Barrows and Gilts - Tao, Xin; Deng, Bo; Yuan, Qizhi; Men, Xiaoming; Wu, Jie; Xu, Ziwei (Frontiers in Microbiology, 2021)
Low protein diets are commonly used in the growing-finishing pig stage of swine production; however, the effects of low dietary protein on the intestinal microbiota and their metabolites, and their association with pig sex, remain unclear. The present study aimed to assess the impact of a low crude protein (CP) diet on the gut microbiome and metabolome, and to reveal any relationship with sex. Barrows and gilts (both n= 24; initial body = 68.33 ± 0.881 kg) were allocated into two treatments according to sex. The four groups comprised two pairs of gilts and barrows fed with a high protein diet (HPD, CP 17% at stage Ⅰ; CP 13% at stage Ⅱ) and a low protein diet (LPD, CP 15% at stage Ⅰ; CP 11% at stage Ⅱ), respectively, for 51 d. Eight pigs in each group were slaughtered and their colon contents were collected. Intestinal microbiota and their metabolites were assessed using 16S rRNA sequencing and tandem mass spectrometry, respectively. The LPD increased intestinal microbiota species and richness indices (P < 0.05) in both sexes compared with the HPD. The sample Shannon index was different (P < 0.01) between barrows and gilts. At the genus level, unidentified Clostridiales (P < 0.05), Neisseria (P < 0.05), unidentified Prevotellaceae (P < 0.01) and Gracilibacteria (P < 0.05) were affected by dietary protein levels. The relative abundance of unidentified Prevotellaceae was different (P < 0.01) between barrows and gilts. The influence of dietary protein levels on Neisseria (P < 0.05), unidentified Prevotellaceae (P < 0.05) and Gracilibacteria (P < 0.01) were associated (P < 0.05) with sex. Metabolomic profiling indicated that dietary protein levels mainly affected intestinal metabolites in gilts rather than barrows. A total of 434 differentially abundant metabolites were identified in gilts fed the two protein diets. Correlation analysis identified that six differentially abundant microbiota communities were closely associated with twelve metabolites that were enriched for amino acids, inflammation, immune, and disease-related metabolic pathways. These results suggested that decreasing dietary protein contents benefitted the intestinal microbiota in growing-finishing pigs, which selectively affected the microbiota and metabolite profiles in gilts.